Burden of renal angiomyolipomas associated with tuberous sclerosis complex: results of a patient and caregiver survey - Anne M. Rentz; Anne M. Skalicky; Zhimei Liu; David W. Dunn; Michael D. Frost; Jo Anne Nakagawa; Judith Prestifilippo; Qayyim Said; James W. Wheless (SpringerOpen, 2018)
Abstract Background Tuberous sclerosis complex (TSC) is a rare genetic disorder characterized by benign tumors in multiple organs, including non-cancerous kidney lesions known as renal angiomyolipomas. This study's objective is to describe the age-stratified morbidity, treatment patterns, and health-related quality of life of TSC patients with renal angiomyolipomas in the United States. A cross-sectional, anonymous web-based survey was conducted with a convenience sample of TSC patients and caregivers identified through a patient advocacy organization. Results Out of the total sample of 676, 182 respondents reported having kidney complications with 33% of the pediatric group and 25% of the adult group with TSC reporting them. Of those with kidney complications, 110 (60%) reported a diagnosis of renal angiomyolipomas, of which 79 (72%) were adult patients and 31 (28%) were pediatric age patients. Eighty-four percent of the pediatric group and 76% of the adult group reported lesions on both kidneys. Of the patients experiencing involvement of only one kidney, 60% of the pediatric group and 21% of the adult group reported having multiple tumors within the affected kidney. Almost all of the sample (99%) reported seeing a physician and having a procedure or test for TSC in the past year. Less than half the respondents (44%) reported being hospitalized in the past year. Thirty-nine percent reported an emergency room visit as well. Compared to scores for patients with kidney disease, the angiomyolipoma adult patients reported significantly lower Mental Component Summary scores on the SF-12. Conclusions Renal angiomyolipomas burden leads to frequent healthcare resource use including hospitalization, invasive treatments, and surgical procedures, which result in an impaired mental health related quality of life.